Comparison of clinical features and prognosis between ultrashort-segment and short-segment hirschsprung disease - Xie, Chuanping; Yan, Jiayu; Guo, Jianlin; Liu, Yakun; Chen, Yajun (Frontiers in Pediatrics, 2023)
Objective To compare the differences in clinical features, postoperative complications, and long-term bowel function outcomes of ultrashort-segment Hirschsprung disease (USHD) and short-segment Hirschsprung disease (SHD). Methods A retrospective study was conducted to compare patients with USHD or SHD who underwent transanal endorectal pull-through (TEPT) at Beijing Children's Hospital between January 2014 and June 2021. Clinical details were collected from medical records. A long-term bowel function questionnaire (age > 4 years old) was completed by the patients' parents. Results A total of 84 patients (USHD = 15, SHD = 69) were included. Age at diagnosis and radical surgery in the USHD group were significantly older than the SHD group (46 [38, 66] vs. 34 [6, 55] months, p = 0.002; 51 [39, 68] vs. 37 [10, 68] months, p = 0.001, respectively). Compared with the SHD group, patients with USHD are more likely to suffer anastomosis leakage and postoperative enterocolitis after TEPT ([3/15, 33.3%] vs. [1/69, 1.4%], p = 0.017; [5/15, 33.3%] vs. [6/69, 8.7%], p = 0.023). In addition, patients in the USHD group are inclined to suffer lower bowel function scores (12.0 [7.5, 18.3] vs. 17 [15, 19], p = 0.018).Patients in the USHD group were more likely to suffer poorer ability to hold back defecation (p = 0.023), soiling (p = 0.011), fecal accidents (p = 0.004), and social problems (p = 0.004). Conclusion Compared with patients with SHD, patients with USHD are diagnosed and performed TEPT at an older age. and they are inclined to suffer postoperative enterocolitis, anastomosis leakage, and poorer long-term bowel function following TEPT.